Lack of taxonomic information from parietal spine size invalidates subspecies in the Atlantic hookear sculpin Artediellus atlanticus. Issue 1 (26th November 2012) - Rees, D.; Byrkjedal, I.
<x xml:space="preserve">Abstract</x> An analysis of 107 individuals of Atlantic hookear sculpin Artediellus atlanticus from the Barents Sea–Svalbard region and from north‐east Greenland shows that the state of the parietal spines, although not randomly distributed geographically, occurs sympatrically. They do not diagnostically describe populations. They are therefore inept for subspecies delimitation into Artediellus atlanticus atlanticus, Artediellus atlanticus corniger and Artediellus atlanticus europaeus. Sympatric occurrence of parietal spine states called for a molecular approach to look for differences at a species level. Sequencing the mitochondrial genes, cytochrome oxidase c subunit I (coI) and cytochrome b (cytb), shows no difference between individuals with different parietal spine size. Thus, there is no evidence of the spine states representing species‐level variation. The study shows that parietal spine size has no taxonomic information for this species. The patterns of variation in parietal spine size differ to some degree between the sexes.